SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF BELIEVERS AND NON-BELIEVERS, SERVING THEIR SENTENCES (AS ILLUSTRATED BY CHRISTIANITY) - Kolesnikova, Natalia; Makarkina, Oksana; Dvoretsky, Dmitry; Manoylova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The object of the work was the research of religiousness as the factor affecting on nature of punishment, future plans, view of life and self-concept. In the work were used the following research methods: personal psychological characteristic examination, assessment of convicted person by the staff, social diagnostics of such factors as conscience of guilt, attitude toward punishment and punishment administration analysis.There were revealed trends in the study testifying an influence of religiousness on persons serving their sentences. Thus, religiousness is a trigger for correctional facility adaptation because there is a decrease of offences and violations of custodial control. Psychological diagnosis showed that the religious have higher opinion of themselves than the irreligious. 63, 2% of the religious have high or average level of inherent value and only 42, 9% of the irreligious have such level of inherent value. The faith promotes positive attitude to life and lower rate of depression among the religious testifies this. Religious convicted persons’ aim in life is to realize their moral standards of higher hierarchical level and this is a favorable background for their life after deinstitutionalization.Thus, research of religiousness as the factor affecting on convicted persons serving their prison terms has showed positive influence of faith on nature of punishment, future plans after deinstitutionalization, view of life and self-concept.